Technology as a Digital Trace in the Sekar Rare-Based Music Composition - Oang Gabriel Matanari; Ni Wayan Ardini; I Wayan Sudirana (Institut Seni Indonesia Denpasar, 2022)
This study aims to analyze Rare Kebyar's musical composition, including instrumentation (form of presentation and instruments used), analysis of song in the work, and a brief analysis of the related video. It is done in a qualitative design. Its data are taken from interviewing, observing, and documenting. Documentation from YouTube is very important in the study. Rare Kebyar's work was done well because of the role of technology in it. Its video is uploaded on YouTube. The analysis of one of the Gending Rare or Sekar Rare in Rare Kebyar's musical works proves that the Balinese artists have a high intellectual level according to their profession. The music video analysis can be a proof that technology is able to go hand in hand with aspects of tradition.